Unveiling Novel Secondary Metabolite Gene Clusters in a Paecilomyces sp. Strain From The Brazilian Amazon Through Computer Aided Genomic Analysis - V. de Oliveira, Daniel; F. Sousa, Thiago; S. P. Sousa, Sabrina; V. de Oliveira, Miguel; dos S. Castro, Gleucinei; Aparecida de Jesus, Maria; F. da Silva, Gilvan (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
The genus Paecilomyces represents a promising source of bioactive secondary metabolites, yet it remains largely underexplored from chemical and genomic perspectives. To address this, a comprehensive genome mining approach was employed to characterize a novel Paecilomyces sp. strain, CMIINPA 1390, isolated from the Brazilian Amazon. Utilizing long-read sequencing, a high-quality, near-chromosome level genome assembly was achieved, comprising six linear scaffolds totaling 31.7 Mb and a circular mitochondrial genome of 52094 bp, with a high BUSCO completeness of 98.7%. Genomic analysis identified 42 biosynthetic gene clusters (BGCs), which is consistent with the genus average. Notably, 100% of these BGCs showed low to no correlation with known biosynthetic pathways, revealing the high potential of this species for the biosynthesis of novel molecules. Gene Cluster Family (GCF) analysis, conducted with 10 reference genomes for the Paecilomyces genus, revealed that among the NRPS-related GCFs, this new Amazonian species presents a singleton associated with nidulanin A biosynthesis. This singleton contained all necessary tailoring genes, but the core nonribosomal peptide synthetase (NRPS) gene exhibited a loss of several modules and domains, retaining only a single module out of the four canonical ones related to nidulanin A biosynthesis. This loss suggests a potential evolutionary divergence, possibly resulting in the production of a shorter or structurally simplified molecule. These findings underscore that Paecilomyces sp. CMI-INPA 1390 is a promising source of diverse and potentially novel secondary metabolites and demonstrate the role of genome mining in unveiling the full biosynthetic potential of filamentous fungi.